Identifying Motivational and Demotivational Productivity Factors in Qatar Construction Projects - Momade, M. H.; Hainin, M. R. (Engineering, Technology & Applied Science Research, 2019)
Motivation is one of the factors that influence productivity. Project management plays a vital role in the success of projects in Qatar construction industry (QCI). It relies profoundly on the team’s active participation and effective performance. Hence it is important to assess the impact of motivation and demotivation on performance. The main objective of this paper is to identify the key factors that cause motivation and de-motivation in QCI. Literature review, surveys with experts and semi-structured interviews were conducted to identify these factors. Using these factors to conduct specific motivational programs will help improve productivity in QCI. Research on motivational factors impacting productivity has not been conducted in Qatar before, so this work will provide insight on how to deal with productivity issues that QCI faces ahead of a major world event that Qatar will host in 2022.